The white elephant - Fleischman, Sid (London: Catnip, 2008)
Run-Run the elephant boy is given a sacred white elephant as a punishment. The elephant is not allowed to work but Run-Run must figure out a way to feed it, himself and his old elephant Walking Mountain. Can Run-Run find a way to make the white elephant disappear? Suggested level: primary, intermediate
Keywords: Children's stories